Revenge A Multilevel Review and Synthesis. [article]. - Jackson, Joshua Condrad
Why do people take revenge? This question can be difficult to answer. Vengeance seems interpersonally destructive and antithetical to many of the most basic human instincts. However, an emerging body of social scientific research has begun to illustrate a logic to revenge, demonstrating why revenge evolved in humans and when and how people take revenge. We review this evidence and suggest that future studies on revenge would benefit from a multilevel perspective in which individual acts of revenge exist within higher-level cultural systems, with the potential to instigate change in these systems over time. With this framework, we can better understand the interplay between revenge's psychological properties and its role in cultural evolution. -- (from the author)